A phase 2 clinical trial of eltrombopag for treatment of patients with myelodysplastic syndromes after hypomethylating-agent failure. Issue 9 (29th July 2019) - Swaminathan, Mahesh; Borthakur, Gautam; Kadia, Tapan M.; Ferrajoli, Alessandra; Alvarado, Yesid; Pemmaraju, Naveen; Bodden, Kristy; Yearby, Brittany; Konopleva, Marina; Khoury, Joseph; Bueso-Ramos, Carlos; Garcia-Manero, Guillermo; et al.
Abstract: Hypomethylating agents (HMA) are the standard of care for treatment of myelodysplastic syndromes (MDS). HMA-failure MDS has extremely poor prognosis. This study was designed to explore the utility of eltrombopag in post-HMA failure MDS patients. Patients were treated in one of two arms: eltrombopag as monotherapy (Arm A), or with continuation of HMA (Arm B). The starting eltrombopag dose was 200 mg orally daily. Twenty-nine patients with a median age of 72 years (42–84) were enrolled. The median number of prior treatment was 1 (1–5). Seven (24%) patients were enrolled in cohort A and 22 (76%) in cohort B. One early death (<30 days) occurred in cohort B due to infection/sepsis. Of 28 evaluable patients, 3 (11%) in cohort B experienced platelet improvement. Median overall survival was 12 months. This study demonstrated modest platelet improvement in some, without evidently increased toxicity or increased risk of leukemia progression. Trial registration: ClinicalTrials.gov identifier: NCT01893372.